1994
DOI: 10.1109/58.330266
|View full text |Cite
|
Sign up to set email alerts
|

1/f noise in etched groove surface acoustic wave (SAW) resonators

Abstract: Measurements of 1/f (or flicker) frequency fluctuations in SAW resonators fabricated with etched groove reflectors on single crystal quartz have shown that the observed noise levels vary inversely with device size. These measurements were made on sixteen 450 MHz resonators of four different sizes. The 1/f noise levels were also evaluated on twenty-eight other SAW resonators ranging in frequency from 401 to 915 MHz. This additional data provides valuable information on the dependence of the flicker noise levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…For V < ε 3 , this is in agreement with the known data for quartz resonators of very high Q as experimental results obtained by Pikal and Walls [8], Parker et al [11] and Vig et al [12], as well as other research groups, indicate.…”
Section: A Calculation Of the Quantum 1/f Sensitivity Limitsupporting
confidence: 92%
See 1 more Smart Citation
“…For V < ε 3 , this is in agreement with the known data for quartz resonators of very high Q as experimental results obtained by Pikal and Walls [8], Parker et al [11] and Vig et al [12], as well as other research groups, indicate.…”
Section: A Calculation Of the Quantum 1/f Sensitivity Limitsupporting
confidence: 92%
“…V is the quartz volume and C is a constant defined by (5) and (6). Here ε 3 is the phonon coherence volume, introduced empirically by Parker et al [10], [11] as a noise coherence volume. Usually, (5) is applicable to high stability BAW resonators, whereas (6) describes SAW resonators.…”
Section: Quartz Crystal Microbalancesmentioning
confidence: 99%
“…Previous studies identified IDT metalizations [ 57 , 58 , 59 ] and the piezoelectric substrate [ 58 , 59 ] as the major sources of flicker noise in SAW devices. Mobile impurities or defects in the substrate cause fluctuations in the local acoustic wave velocity [ 59 ], thus leading to random phase fluctuations.…”
Section: Phase Noise In Magnetic Saturationmentioning
confidence: 99%
“…Mobile impurities or defects in the substrate cause fluctuations in the local acoustic wave velocity [ 59 ], thus leading to random phase fluctuations. In addition, due to a very strong sensitivity to surface conditions, the surface acoustic wave velocity is modulated by gas molecules adsorbed onto the surface [ 58 , 59 ]. For example, as early as 1979, it was reported that the flicker noise depends on the cleanliness of the surface [ 60 , 61 ].…”
Section: Phase Noise In Magnetic Saturationmentioning
confidence: 99%